Potential Valuation Of Plants Based On Utilization Of Plants, Local Wisdom and Local Resident Attitude about Plant Conservation in Silokek National Geopark - Dina Hayati Putri; Tesri Maideliza; Mahdi Mahdi (Jurnal Biologi Universitas Andalas, 2021)
The objectives of this study was to evaluate the utilization of plants, local wisdom and tribe attitudes about plant conservation by the people in Silokek National Geopark. This research used survey method. These data were collected by using Pebble Distribution Method (PDM) and Quisioner. And then, data had been calculated by calculating the value of Local User’s Value Index (LUVI). The result indicated that local people utilizing plants is for herbal medicine 83%. Cyclea barbata is spesies with having the highest LUVI (0.137), followed by Artocarpus elasticus used for furniture (LUVI= 0.060), Styrax sumatrana (LUVI= 0.126) used for ritual, and Imperata cylindrica (LUVI= 0.073) used for livestock feed. And The result showed at least three local wisdom that possible to be integrated to plant conservation such as planting the plants, selectively harvest by select cutting and timing, and special treatment before used the plants like shalawat nabi reading. For tribe attitudes indicated people in Silokek National Geopark more 90% agree for conservation policy in that area.Keywords : Local User’s Value Index (LUVI), Pebble Distribution Method (PDM), Silokek National Geopark.